Analysis on structure reliability of solar powered water treatment device (SWAD) prototype - Ismail I.N.B.; Khean F.F.; Zawawi M.H.; Zahari N.M.; Abidin S.Z.; Yusairah W.N.; Zuhdi A.W.M.; Eqwan M.R.; Mohamed H.; Ramli M.Z.; Mansor M.H.; Syaifoelida F.; et al. (American Institute of Physics Inc., 2023)
An improved water quality is very essential element for aquaculture industry. Solar powered water treatment device is basically a floating water filter which operates in a self-sustainable way on calm water body such as lake. The objective of building a prototype solar powered water treatment device (SWAD) is to have an independent power supply without relying from the grid to run the water treatment process through filtration. The project undergoes preliminary design, CAD drawings with simulation, prototype fabrication and prototype testing. By utilizing CAD simulation, through analysis has been done to determine the suitable size and the type of material for the device structure. The criteria of the structure must be light weight, sturdy and not reactive to water. The structure needs to withstand the total weight of the prototype plus it can float at the water surface. 2019 Author(s).